Aplikasi Monitoring dan Penentuan Ayam Petelur Afkir Menggunakan Naive Bayes Classifier - Ardenno Rama Rasendriya (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2024)
Animal husbandry is the activity of breeding and cultivating farm animals in order to obtain benefits and results from these activities. The most widely cultivated livestock is chicken. One of the companies that utilize chicken is PT Reza Perkasa. The management of data records of laying hens in the company still does not have a system and still uses excel reports every week. Farmers in determining the chicken afkir is still in the form of traditional records. The problem can be solved by making a monitoring application and a system for determining abandoned laying hens using the naïve bayes method. It is expected that with the monitoring application, the general manager can quickly monitor in real-time, so that for the needs of chickens that are useful for improving production quality quickly without the need to wait for manual reports from the head of the cage.